Biochemical assessment of nephroprotective and nephrocurative activity of Withania somnifera on gentamicin induced nephrotoxicity in experimental rats - Kushwaha, Vimlesh; Sharma, Monica; Vishwakarma, Pinki; Saini, Manish; Saxena, Kuldeep (International Journal of Research in Medical Sciences, 2016)
Background: Renal diseases are among the commonest cause of hospitalization in most of the countries. Acute renal failure (ARF) is a common and serious renal problem having high morbidity and mortality rate. So, prevention of occurrence and progression of acute renal failure (ARF) has become a very important issue. However modern system of medicine lacks reliable nephroprotective drugs. Ashwagandha (Withania somnifera), a traditional Indian plant having antioxidant property may be used for nephroprotection. Methods: The study was carried out in two phases. In phase 1, evaluation of nephroprotection was done. 54 rats were randomised in 3 groups named G10, G20 and G30 according to 10, 20 and 30 days of treatment. In each of the main groups, rats were randomly assigned to any of the three subgroups i.e. control C group (received normal saline (2ml/100gm/day) orally once a day consecutively for test duration), gentamicin treated GT (received normal saline (2ml/100gm/day) orally once a day consecutively for test duration, Injection gentamicin (40mg/kg) was given intraperitonealy once daily for last five days) and W. Somnifera treated WST group (received W. somnifera orally (500mg/kg/day) as a single dose in morning for the test duration and injection gentamicin (40mg/kg) was given intra-peritonealy once daily for last five days). Rats were sacrificed 24 hours after the last dose of gentamicin injection (on 11th, 21st and 31st day). In Phase-2 nephrocurative activity of W. somnifera was compared with the spontaneous reversal of gentamicin induced nephrotoxicity. 72 rats were randomized into two groups. In Group-1: 36 rats received intra-peritoneal gentamicin for five days in a dose of 40 mg/kg. In Group-2: 36 rats received intra-peritoneal gentamicin for five days in a dose of 40 mg/kg. From the 5th day onward these rats received W. Somnifera orally in a dose of 500mg/kg/day till the rats are sacrificed. Six rats from each group were sacrificed on 3rd, 5th, 7th, 10th, 12th and 14th day after administration of last dose of Gentamicin. Blood sample were taken for evaluation of BUN and serum creatinine Results: BUN and serum creatinine values were significantly low as compared to GT group in all test duration in phase-1. In phase two there was no significant difference of these markers in two groups. Conclusions: Withania Somnifera root extract have nephroprotective activity against gentamicin induced nephrotoxicity.